Fenomena Tubuh Perempuan dalam Anime Kimi no Na Wa - Nu'man Zamaludin; Tisna Prabasmoro; Ari Jogaiswara Adipurwawidjana (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2024)
Indonesia, with its multicultural society, has many traditions/ Kimi no Na Wa (Your Name) is an anime displaying the reality of gender and women in a complex way. This complexity can be seen in the narrative displayed, namely the exchange of bodies between female and male characters. This article questions the phenomenon of women and their bodies in this anime. The analysis used phenomenological theory of perception with a descriptive analysis method. The result shows that the phenomenon of body exchange between men and women confirms gender issues that are not tied to sex. The exchange of bodies also indicates women's endeavor to change them from what were previously associated with rural and traditional into modern ones. In addition, the phenomenon of body exchange also emphasizes that the body is an essential element of human existence.